1848 Ala. Acts 121–22, An Act To Prevent the Storage of Gun-powder in Larger Quantities Than One Hundred Pounds Within the City of Mobile, § 1 - (:unkn) unknown (General Publisher, 1848)
Prohibited any person or persons from receiving, keeping, or storing in any building within three miles of the Mobile River or Bay, gun-powder, gun-cotton, or other explosive material in larger quantities than one hundred pounds.
--
Keywords: GUN POWDER STORAGE